The implementation of the SAGUSAKA program as a strategy to foster writing habits among students - Istiqomah, Yulian; Ningrum, Dian Fitri (COPE: Caraka Olah Pikir Edukatif, 2026)
This study aims to describe the implementation of the One Week, One Work (SAGUSAKA) program and analyze its impact on students’ writing skills at MTs Negeri 2 Bantul. This study employs a descriptive qualitative approach with seventh-, eighth-, and ninth-grade students as subjects. Data were collected through observation, questionnaires, and documentation of student works, then analyzed using descriptive-interpretive methods with triangulation techniques to ensure data validity. The results indicate that the SAGUSAKA program increases the frequency of student writing, improves the quality of their writing, and serves as a means of fostering writing literacy. This program also has a positive impact on students’ motivation and self-confidence in writing, thereby helping to foster a culture of literacy at the school. Supporting factors for the program include an organized school mentoring system and the publication of students’ work. Overall, the SAGUSAKA program serves as a habit-forming strategy to improve the writing skills of junior high school/MTs students and has the potential to be implemented in other educational institutions.